The Analysis of Students’ Critical Thinking Through Poem in The Scheme of Informal Class: (A Descriptive Qualitative Research of 6th Grade Students in Informal English Class of Karang Taruna RW.05) - Yusyfiana, Ana; Masrifdah, Siti (CV RIFAINSTITUT, 2024)
This study analyses the data to knowing level of 6th grader students’ level of critical thinking and their attitude and responses towards the class. Three students from the English club Karang Taruna RW.05 with different cognitive abilities were taken as samples. The data were obtained through poem, which the prime data were taken from observation dan documentation, while the secondary data were taken from interview. From the research results it was found that every child has differences in the way of thinking and understanding a problem, which are at levels one and two according to Bloom’s taxonomy.